Project-Based Learning (PBL) in Nepalese EFL Classroom - Bastola, Ganesh Kumar (Dristikon: A Multidisciplinary Journal, 2021)
Project-based learning is an innovative method to improve language skills. This study explores the five assets of project-based learning in the Nepalese context. It aims to examine how different dynamics of projects help students overcome their language learning difficulties and to show the relevancy of Project-Based Learning despite having many approaches and techniques in the anti-method era. Data for this study were collected both from primary and secondary sources. For eliciting primary information, I interviewed two of the EFL teachers and for the secondary data, I consulted research articles, books, dissertations, and reports related to project-based learning. I also employed the document analysis method in the paper since it is a theoretical review-based article where the researcher coded, thematized, and analyzed very sequentially to elicit meaning, gain understanding, and develop empirical knowledge about project-based learning. Innovative and learner-friendly curriculum demands for practical, pedagogical and project-based engagement in the 21st-century classroom which has seriously been ignored in the Nepalese EFL classroom. Noticing the unexplored status of the project-based learning approach, I stressed exploring the relevancy of PBL in the EFL classroom. More specifically, the prior methods used for achieving the expected outcomes of the paper are synthesis, deduction, analysis, interpretation and generalization. Findings indicate that project-based learning is an alternative tool and the best option for students to enhance their pedagogical content knowledge, creativity, and critical thinking.